Answer:
![\begin{cases}a_1 = 2\\\\a_(n) = -4*a_(n-1)\end{cases}](https://img.qammunity.org/2021/formulas/mathematics/high-school/64ism599c7j3eezxujd9da0o2a69j37ztk.png)
============================================
Step-by-step explanation:
The first line of the answer says "the first term is 2".
The second line says "take any term and multiply by -4 to get the next term".
The
represents the nth term while
is the term just before it.
The second line shown above is the same as writing
![a_(n+1) = -4*a_n](https://img.qammunity.org/2021/formulas/mathematics/high-school/qtbpy3od4stygu579k9p26c3ih7bzbabyl.png)
---------------
The -4 is found by dividing any term over its previous one
-8/2 = -4
32/(-8) = -4
-128/32 = -4
512/(-128) = -4
This shows the common ratio is -4 and this sequence is geometric.